What's politics got to do with it: Nutrition and the policy agenda - Fritschel, Heidi; Vivalo, Julia; Gustafson, Sara; Shelton, Peter; Sullivan, Rebecca Harris; Yin, Sandra; Johnson, Ian; Lippincott, Don; Weeks, Jennifer (International Food Policy Research Institute, 2013)
Recent experience has shown that as countries get richer, nutritional status does not necessarily improve. In a recent article in the journal The Lancet, IFPRI researchers and others explain that creating the right conditions for nutritional advances often requires political action. The feature article in this issue of Insights looks at how some developing countries and regions—Ghana, Peru, Thailand, and the state of Maharashtra, India—have made nutrition a political priority and how they’ve turned political commitments into widespread changes on the ground. The rest of this issue of Insights describes other important IFPRI research, touching on many different areas related to food policy.